Familial Hyperparathyroidism. Issue 5766 (10th July 1971) - Marsden, P.; Anderson, J.; Doyle, D.; Morris, B. A.; Burns, D. A.
Abstract : Twenty-eight members of a family over three generations were studied; six of them had hyperparathyroidism. Four of the six were siblings and one of these had suffered from recurrent hyperparathyroidism. No member of the family showed any other significant endocrine disturbance or active peptic ulceration. Attention is drawn to the prominent lack of symptoms despite dangerous levels of hypercalcaemia and advanced disease with the consequent need for estimation of serum calcium levels in all close relatives. Multiple gland involvement is common in familial hyperparathyroidism and is often coupled with a tendency to recurrence, necessitating long-term follow-up. Histological appearances vary considerably, and the risk of recurrence is not limited to cases showing primary chief cell hyperplasia, with the implication that resection of three parathyroid glands and part of the remaining gland may be the treatment of choice in all cases of familial hyperparathyroidism when multiple gland involvement is found.